2005
DOI: 10.4038/jnsfsr.v33i4.2111
|View full text |Cite
|
Sign up to set email alerts
|

General Features and Fisheries Potential of Palk Bay, Palk Strait and its Environs

Abstract: The issue of possible social and environmental impacts of the shipping canal proposed for the Palk Bay and Palk Strait area is a much debated topic. Therefore it is necessary to explore the general features of the said area to assess such impacts when formulating the development and management programmes relevant to the area. This paper discussed the general features of the area, its environmental and ecological condition and the fisheries potential in detail so as to give some insight to the reader on this im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…H. fuscus has been reported from shallow protected bays with calm water, algal reefs and seagrass beds up to a maximum depth of 10m (Lourie et al, 2004). In Sri Lanka, it is known to occur around the Jaffna Peninsula (Vincent, 1994a(Vincent, & 1994b, an area with shallow lagoons and extensive seagrass habitats (Sivalingam, 2005 (Lourie et al, 2004;Harasti et al, 2012).…”
Section: Distribution Patternsmentioning
confidence: 99%
“…H. fuscus has been reported from shallow protected bays with calm water, algal reefs and seagrass beds up to a maximum depth of 10m (Lourie et al, 2004). In Sri Lanka, it is known to occur around the Jaffna Peninsula (Vincent, 1994a(Vincent, & 1994b, an area with shallow lagoons and extensive seagrass habitats (Sivalingam, 2005 (Lourie et al, 2004;Harasti et al, 2012).…”
Section: Distribution Patternsmentioning
confidence: 99%
“…358 in the Ramsethu region (square II). Also see similar representation in Sivalingam (2005) B a y o f B e n g a l ( B o B ) i n t h e e a s t . T h e Rameswaram (Pamban) Island of India, Ramsethu (Adam's Bridge), and Mannar Island of Sri Lanka act as physical barriers that inhibit the exchange of waters between the GoM and the PB (Fig.…”
Section: Introductionmentioning
confidence: 79%
“…Conversely, Sivalingam (2005) reported salinity values for wet season and dry season at some locations in the Jaffna estuary, which were 10.3 ppt in December and 45.5 ppt in June respectively. Sachithananthan (1969) also reported that the salinity of the Jaffna estuary varied from a maximum of 45·5 ppt during July-August to a minimum of 10·4 ppt during December.…”
Section: Discussionmentioning
confidence: 99%
“…The ecology of the estuary is determined to a large extent by freshwater inputs (Postma, 1981;Ittkoot et al, 2000). Spatial and temporal variations of the physico-chemical parameters in the estuaries of Sri Lanka have been analysed by several authors (Sachithananthan, 1969;Sachithananthan and Perera, 1970;Sivalingam, 2005;Niroshana et al, 2013).…”
Section: Introductionmentioning
confidence: 99%